The Existing of Naqshbandi Tariqa and Its Influence on Socio-Cultural Life of the Sakai People in Bengkalis Regency - Amrizal Isa; Riki Astafi (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2019)
This study aims to determine the development of the Naqshabandiyah Tarekat and its influence on the socio-cultural life of the Sakai people in Bengkalis Regency. The findings of this study are that the Naqshabandiyah Tarekat entered and developed among the Sakai Tribe in a number of different regions, but not at the same time with different carrier figures. If mapped, there are three main lines (networks), namely the first line of the Ibrahim Caliph in 1912 at Bomban Potani in the area of Bathin Solapan. Second, the path of Sheikh Imam Sabar Al-Kholidi in 1925 in Beringin Village, Talang Muandau area. Third, Caliph Mahmud in 1947 in Tasik Serai. The presence of the Naqsyabandiyah Tarekat in the onder region of the Mandau district can be well accepted by the Sakai Tribe. This is evidenced by the existence of approximately 11 suluk houses in the Sakai Tribe domicile today. The teachings of the Naqshabandiyah Tarekat greatly influenced the socio-cultural life of the Sakai Tribe. Most of them have abandoned the bad habits that have been practiced and become devout Muslims. Islamic values are very thick coloring their social system both concerning the system of marriage and family life, social relations, political and government leadership, customs and traditions, and the economy.